Health screening clinic to reduce absenteeism and presenteeism among NHS Staff: eTHOS a pilot RCT - Rachel Adams; Rachel E Jordan; Alisha Maher; Peymane Adab; Timothy Barrett; Sheriden Bevan; Lucy Cooper; Ingrid DuRand; Florence Edwards; Pollyanna Hardy; Ciara Harris; Nicola R Heneghan; et al. (NIHR Journals Library, 2024)
Background Staff sickness absenteeism and presenteeism (attending work while unwell) incur high costs to the NHS, are associated with adverse patient outcomes and have been exacerbated by the COVID-19 pandemic. The main causes are mental and musculoskeletal ill health with cardiovascular risk factors common. Objectives To undertake a feasibility study to inform the design of a definitive randomised controlled trial of the effectiveness and cost effectiveness of a health screening clinic in reducing absenteeism and presenteeism amongst the National Health Service staff. Design Individually randomised controlled pilot trial of the staff health screening clinic compared with usual care, including qualitative process evaluation. Setting Four United Kingdom National Health Service hospitals from two urban and one rural Trust. Participants Hospital employees who had not previously attended a pilot health screening clinic at Queen Elizabeth Hospital Birmingham. Interventions Nurse-led staff health screening clinic with assessment for musculoskeletal health (STarT musculoskeletal; STarT Back), mental health (patient health questionnaire-9; generalised anxiety disorder questionnaire-7) and cardiovascular health (NHS health check if aged ≥ 40, lifestyle check if < 40 years). Screen positives were given advice and/or referral to services according to UK guidelines. Main outcome measures The three coprimary outcomes were recruitment, referrals and attendance at referred services. These formed stop/go criteria when considered together. If any of these values fell into the 'amber' zone, then the trial would require modifications to proceed to full trial. If all were 'red', then the trial would be considered unfeasible. Secondary outcomes collected to inform the design of the definitive randomised controlled trial included: generalisability, screening results, individual referrals required/attended, health behaviours, acceptability/feasibility of processes, indication of contamination and costs. Outcomes related to the definitive trial included self-reported and employee records of absenteeism with reasons. Process evaluation included interviews with participants, intervention delivery staff and service providers. Descriptive statistics were presented and framework analysis conducted for qualitative data. Due to the COVID-19 pandemic, outcomes were captured up to 6 months only. Results Three hundred and fourteen participants were consented (236 randomised), the majority within 4 months. The recruitment rate of 314/3788 (8.3%) invited was lower than anticipated (meeting red for this criteria), but screening identified that 57/118 (48.3%) randomised were eligible for referral to either general practitioner (81%), mental health (18%) and/or physiotherapy services (30%) (green). Early trial closure precluded determination of attendance at referrals, but 31.6% of those eligible reported intending to attend (amber). Fifty-one of the 80 (63.75%) planned qualitative interviews were conducted. Quantitative and qualitative data from the process evaluation indicated that the electronic database-driven screening intervention and data collection were efficient, promoting good fidelity, although needing more personalisation at times. Recruitment and delivery of the full trial would benefit from a longer development period to better understand local context, develop effective strategies for engaging with underserved groups, provide longer training and better integration with referral services. Delivery of the pilot was limited by the impact of COVID-19 with staff redeployment, COVID-research prioritisation and reduced availability of community and in-house referral services. While recruitment was rapid, it did not fully represent ethnic minority groups and truncated follow-up due to funding limitations prevented full assessment of attendance at recommended services and secondary outcomes. Conclusions There is both a clinical need (evidenced by 48% screened eligible for a referral) and perceived benefit (data from the qualitative interviews) for this National Health Service staff health screening clinic. The three stop/go criteria were red, green and amber; therefore, the Trial Oversight Committee recommended that a full-scale trial should proceed, but with modifications to adapt to local context and adopt processes to engage better with underserved communities. Trial registration This trial is registered as ISRCTN10237475. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 17/42/42) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 23. See the NIHR Funding and Awards website for further award information. Plain language summary Sickness absenteeism and presenteeism (attendance at work while ill, with poor work performance) are major problems in the NHS and associated with worse patient health care. The most common causes of NHS staff sickness absenteeism and presenteeism are muscular complaints and mental ill health. Poor lifestyle and illnesses associated with heart disease are also important factors. Staff health checks might improve the health of NHS staff, but no studies have included screening tests to address the most common causes of poor staff health. This pilot study tested whether it would be possible to deliver a randomised controlled trial of an NHS staff health screening clinic, where some people get the screening check and others do not (chosen at random, like flipping a coin). We used an electronic database to capture all data. Participants completed initial questionnaires either at home or at work, then attended a face-to-face screening clinic using recognised screening questionnaires and tests to detect problems with muscular, mental or heart health. We considered how NHS staff and healthcare organisations would want the screening clinic and trial to run, how a diverse range of NHS staff could best be approached, how many staff might need to be invited and what their healthcare needs would be. The study ran in four UK NHS hospitals during the COVID-19 pandemic. Two hundred and thirty-six NHS staff participated, but early trial closure due to the pandemic meant that some results were unavailable. For the primary feasibility outcomes, although recruitment rates of around 8% were lower than anticipated, half of staff screened needed referral for further health care and one-third reported intending to attend. Staff felt that the clinic addressed an important health need. The Trial Oversight Committee recommended proceeding to a full-scale trial but with modifications to address findings from the process evaluation, including ways to encourage a wider group of NHS staff to take part. Scientific summary Background Staff sickness absenteeism and presenteeism (attending work while unwell) incur high costs to the NHS, are associated with adverse patient outcomes and have been exacerbated by the COVID-19 pandemic. The main causes are mental and musculoskeletal ill health with cardiovascular risk factors also common. Objectives The aim of this pilot trial was to assess the feasibility of a definitive randomised controlled trial (RCT) evaluating the clinical and cost effectiveness of a health screening clinic compared to usual care, in reducing sickness absenteeism and presenteeism amongst NHS staff. The key objectives were to: describe recruitment rates describe participant characteristics and assess generalisability compared to the hospital workforce describe intervention screening assessment results describe recommended referrals and their uptake assess the feasibility of measuring the outcomes relating to the definitive trial, and obtain an estimate of the standard deviation of the proposed primary outcomes for a full RCT assess levels of contamination between intervention and usual care arms to inform RCT design (individual vs. cluster RCT) describe and explain the fidelity to the intervention and evaluate the barriers and enablers to participation describe the views, experiences and satisfaction of participants and those delivering the health checks quantify the costs of undertaking the screening service and its consequences.